Comparing the Efficacy of IV Ibuprofen and Ketorolac in the Management of Postoperative Pain Following Arthroscopic Knee Surgery. A Randomized Double-Blind Active Comparator Pilot Study - Uribe, Alberto A.; Arbona, Fernando L.; Flanigan, David C.; Kaeding, Christopher C.; Palettas, Marilly; Bergese, Sergio D. (Frontiers in Surgery, 2018)
Introduction: Acute postoperative pain following knee arthroscopy is common in orthopedic surgeries. Managing pain postoperatively combines usage of opioids and non-steroidal anti-inflammatory drugs. The aim of this clinical study was to assess the efficacy of two different analgesic treatment regimens: intravenous (IV) ibuprofen and IV ketorolac for the treatment of postoperative pain pertaining to arthroscopic knee surgery. Methods: This was a single center, randomized, double-blind, parallel, active comparator clinical pilot study. Subjects were randomized to receive either IV ibuprofen, administered as two 800 mg doses or IV ketorolac, administered as a single 30 mg dose. Subjects in the ibuprofen group received 800 mg of IV ibuprofen within 2 h prior to surgery and a repeated second dose 4 h after the initial dose if they had not been discharged. Subjects in the ketorolac group received IV ketorolac 30 mg at the end of surgery, as per the manufacturer's recommendations. Pain assessments and opioid consumption data were collected up to 24 h postoperatively. Results: Of 53 randomized subjects, 51 completed the study. There were 20 subjects in the ibuprofen group and 31 subjects in the ketorolac group. The median (IQR) visual analog scale (VAS) pain score at resting upon post-anesthesia care unit (PACU) arrival was 33 (12, 52) vs. 9 (2, 25) (p = 0.0064) for the ketorolac and ibuprofen group, respectively. The median (IQR) visual analog scale (VAS) pain score at movement upon PACU arrival was 38 (20, 61) vs. 15 (6, 31) (p = 0.0018) for the ketorolac and ibuprofen group, respectively. Median VAS pain scores during movement taken at subsequent 30 min intervals in the ibuprofen group were less than half that of those reported in the ketorolac group for up to 90 min after arriving in PACU. The median VAS pain scores at rest and movement in the course of 120 min−24 h after PACU arrival was not statistically significant in both groups. Rescue opioid medication during PACU stay was required in 55.0% (N = 11) and 83.9% (N = 26), with a mean amount of narcotic consumption (oral morphine conversion) of 5.53 ± 5.89 mg vs. 19.92 ± 15.63 mg for the ibuprofen and ketorolac group, respectively (P < 0.001). However, opioid consumption during the first 24 h after PACU discharge was not statistically significant (p-value = 0.637). The mean time to first rescue medication was 77.62 ± 33.03 and 55.78 ± 35.37 for the ibuprofen and ketorolac group, respectively (p-value = 0.0456). There were no significant differences in patient satisfaction and documented adverse events during the first 24 h. Conclusion: This pilot study showed that the use of preemptive IV ibuprofen 800 mg could be considered to reduce postoperative pain and opioid consumption. Future prospective clinical trials using similar regimens should be conducted in order to gain a better understanding of how to best provide perioperative analgesic regimens. Clinical Trial Registration:www.ClinicalTrials.gov, identifier NCT01650519.